In Search of Instruments. Business and Ethics Halfway - van Luijk, Henk J. L. (Journal of business ethics, 2000)
Business ethics has gradually acquired a stable status, both as an academic discipline and as a practice. Stakeholdership is recognised as a guiding concept, business has widely accepted that it has a license to operate to win from society at large, and operational instruments such as codes of ethics and forms of ethical auditing and accounting take shape more and more. Yet lacunae remain. Three are mentioned explicitly. Business ethics has to improve its relations with business law, the concept of competition deserves much more ethical attention than it has received up to now, and the shifting relations between the market, governmental agencies and civil society require the elaboration of an institutional business ethics.